Latent scrutiny: personal archives as perpetual mementos of the official gaze - Wilson, Jacqueline Z.; Golding, Frank (Archival Science, 2016)
This article examines the significance, in the lives of those who experienced out-of-home care as children, of the archived records of their institutionalisation. The affective ramifications of accessing the records as adults are discussed, with especial focus on the records’ capacity to revive past suffering. Drawing on the work of Bruner (Crit Inq Autumn 1–21, 1991 , Consumption and everyday life, Sage, London, 1997 ) and MacIntyre (After virtue: a study in moral theory, University of Notre Dame Press, Notre Dame, 1981 ), a ‘narrative’ model of the self is utilised to account for the negative effect of systemic flaws in the records’ original composition. Such flaws, it is argued, have the potential to disrupt the individual’s sense of self. Both the authors, who experienced out-of-home care as children, present their own experiences of accessing the records, as case studies. The records’ manifold inaccuracies and inadequacies are interpreted in the light of prevailing welfare practices, in particular a highly damaging judgemental paradigm of gendered and moralistic assumptions of the inferior character of those in care. The authors conclude by arguing that research into the archives should involve the direct participation, as ‘insider researchers’, of those who experienced the matters contained in the records. Such participation is essential if the process of revealing and interpreting the archives is to maintain the dignity of the records’ subject individuals, and ensure the integrity of the research.